FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BBLR PADA IBU HAMIL DENGAN PRE EKLAMSIA BERAT DI RS MARGONO SOEKARJO PURWOKERTO - Sumarni, SSiT., M.Keb - (Viva Medika, 2018)
ABSTRCT Pregnant women tend to beprone to pre-eclampsia if they have predisposing factors as follows; Nulipara, multiple pregnancy, age <20 or> 35 years, history of pre-eclampsia, eclampsia in previous pregnancies, family history of pre-eclampsia, kidney disease, hypertension and diabetes mellitus that existed before pregnancy, obesity. Objective: factors relation with LBW in pregnant women with savere pre-eclampsia. Research method: This study used descriptive explanatory. The total population of 57 pregnant women with pre-eclampsia at Margono Soekardjo Hospital in Purwokerto, the sample was taken by random sampling method, data analysis used chi square test with confidence level p = 0.05. The results showed that there was a relationship between parity with LBW(p:0,014;OR:4.071) and there was no relationship between age and history of pre-eclampsia and LBW (P:0.322;0.117) Conclusion: there was a relationship between parity with LBW.